Regenerative medicine strategies for hair growth and regeneration: A narrative review of literature - Shimizu, Yusuke; Ntege, Edward Hosea; Sunami, Hiroshi; Inoue, Yoshikazu (Regenerative therapy, 2022)
Hair loss, or alopecia, is associated with several psychosocial and medical comorbidities, and it remains an economic burden to individuals and the society. Alopecia is attributable to varied mechanisms and features a multifactorial predisposition, and the available conventional medical interventions have several limitations. Thus, several therapeutic strategies for alopecia in regenerative medicine are currently being explored, with increasing evidence suggesting that mesenchymal stem cell (MSC) implantation, MSC-derived secretome treatment, and blood-derived platelet-rich plasma therapies are potential treatment options. In this review, we searched the Cochrane Library, MEDLINE (PubMed), EMBASE, and Scopus using various combinations of terms, such as “stem cell,” “alopecia,” “hair loss,” “Androgenetic alopecia,” “male-pattern hair loss,” “female-pattern hair loss,” “regenerative hair growth,” “cell therapy,” “mesenchymal stem cells,” “MSC-derived extracellular vesicles,” “MSC-derived exosomes,” and “platelet-rich plasma” and summarized the most promising regenerative treatments for alopecia. Moreover, further opportunities of improving efficacy and innovative strategies for promoting clinical application were discussed. •Alopecia poses significant human health risks and is an economic burden to society.•Previous research yielded few conventional treatments with irrefutable limitations.•Regenerative medicine therapeutic products are evidently highly promising options.•The products are mainly MSC transplants, MSC-derived Evs, or PRP formulations.•EVs and PRP are more attractive strategies offering multifarious clinical advantages.